FAKTOR-FAKTOR YANG MEMENGARUHI CONSUMER PURCHASE DECISION TERHADAP PRODUK PARFUM HMNS - Data Tsabitha; Margaretha Pink Berlianto (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
The purpose of this study is to analyze the effect of Visual Packaging Design, Verbal packaging design, Packaging Benefits, Perceived Quality, & Price on Consumer Purchase Decisions on HMNS products. This study uses a quantitative approach with a google form questionnaire, distributed to respondents who are consumers of HMNS perfume who lived in Jakarta. The number of samples used is 200 respondents, then analyzed through PLS-SEM using SmartPLS 3.0. The results showed that Packaging Design Visual, Packaging Design Verbal, Packaging Benefits, Perceived Quality, and Price have a positive effect on Consumer Purchase Decisions. This means, that the higher the Visual Packaging Design, Verbal Packaging Design, Packaging Benefits, Perceived Quality, and Price of HMNS perfume products, the higher the Consumer Purchase Decision. The main limitations of this study the use of online questionnaire to collect data, that which limits supervision in the data entry process to ensure whether the data given is correct according to the directions. The results showed that Packaging Design Visual, Packaging Design Verbal, Packaging Benefits, Perceived Quality, and Price had a positive effect on Consumer Purchase Decisions. Which means, the higher the Visual Packaging Design, Verbal Packaging Design, Packaging Benefits, Perceived Quality, and Price of HMNS perfume products, the higher the Consumer Purchase Decision. This research is expected to be useful for HMNS companies and other industry players, adding knowledge and insight, especially in the field of management, as well as being a reference for further researchers.BAHASA INDONESIA ABSTRACTTujuan dari penelitian ini adalah untuk mengetahui pengaruh antara Packaging Design Visual, Packaging Design Verbal, Packaging Benefits, Perceived Quality, dan Price terhadap Consumer Purchase Decision. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pengumpulan data kuesioner yang disebar kepada responden yang merupakan konsumen produk parfum HMNS yang berdomisili di Jakarta. Jumlah sampel yang digunakan sebanyak 200 responden, kemudian di analisis melalui PLS-SEM menggunakan SmartPLS 3.0. Hasil penelitian menunjukkan bahwa Packaging Design Visual, Packaging Design Verbal, Packaging Benefits, Perceived Quality, dan Price berpengaruh positif terhadap Consumer Purchase Decision. Artinya, semakin tinggi Packaging Design Visual, Packaging Design Verbal, Packaging Benefits, Perceived Quality, dan Price produk parfum HMNS, maka semakin tinggi pula Consumer Purchase Decision. Keterbatasan utama pada penelitian ini yaitu, pengambilan data dengan kuesioner online, sehingga peneliti mengalami keterbatasan dalam mengawasi proses pengisian data untuk memastikan apakah data yang diisikan sudah benar sesuai arahan, serta keterbatasan dalam menjelaskan secara langsung mengenai pertanyaan-pertanyaan yang mungkin dianggap kurang jelas. Hasil penelitian menunjukkan bahwa Visual Desain Kemasan, Desain Kemasan Verbal, Manfaat Kemasan, Kualitas yang Dirasakan, dan Harga memiliki efek positif pada Keputusan Pembelian Konsumen. Artinya, semakin tinggi Desain Kemasan Visual, Desain Kemasan Verbal, Manfaat Kemasan, Kualitas yang Dirasakan, dan Harga produk parfum HMNS, semakin tinggi Keputusan Pembelian Konsumen. Penelitian ini diharapkan dapat bermanfaat bagi perusahaan HMNS dan pelaku industri lainnya, menambah pengetahuan dan wawasan, khususnya di bidang manajemen, serta menjadi acuan bagi penelitian lebih lanjut.